The Role Of Emotion Regulation And Peer Social Support On Academic Stress Of Junior High School Students - Karamina, Ponti Almas; Martani, Wisjnu (Al Huwiyah: Journal of Woman and Children Studies, 2023)
Adolescents aged 13-15 years old experience a shift from childhood, one of it is a more independent academic life. In this time, adolescents are prone to experience academic stress. This study aimed to examine the role of emotion regulation and peer social support in junior high school students' academic stress. The participants of this study were 165 public junior high school student in the city of Yogyakarta who were chosen using non-random sampling method. The hypothesis of this study suggests that emotion regulation and peer social support play a role on academic stress in junior high school students. Instruments of this research are emotion regulation scale, peer social support scale, and academic stress scale. The data were analysed using multiple regression, which showed that emotion regulation and peer social support explained 20.9% of academic stress variance, with emotion regulation explaining 20.5% and peer social support explaining 0.4%. Therefore, future studies are needed to explore other factors that could play a role in junior high school students' academic stress.